(untitled) (The Peerian Journal, 2023)
Management is not a process unique to production. Perhaps it is very important to properly organize the management of social spheres, as well as in the educational system. Currently, the movement of a scientific approach to the management of a single pedagogical process has increased. This is very important for the formation of personnel with high intellectual potential. The article covers the concepts of educational institution management.